Aspect-Oriented Business Process Modeling Approaches: An assessment of AOP4ST - Pinciroli, Fernando (2017)
Aspect-oriented business process modeling (AOBPM) is an emerging discipline which has recently attracted the attention of researchers and professionals. In 2014, Amin Jalali reviewed the state of the art of AOBPM and proposed a framework to assess the available approaches. We have developed AOP4ST, an aspect-oriented process for the software development life cycle, which includes the business process modeling as its first phase, and which follows the Jalali’s recommendations. In this paper, we present the assessment of the AOP4ST’s business modeling capability by comparing it with all of the original proposals assessed by Jalali’s framework. Finally, we present ongoing work for the improvement of our approach on its AOBPM capabilities and its ability to detect and separate concerns at early stages of the development.